2021
DOI: 10.1021/acs.jpcc.1c00632
|View full text |Cite
|
Sign up to set email alerts
|

Energy Component Analysis of Electric Field-Induced Shape Change in Water Nanodroplets

Abstract: We present a comprehensive classical molecular dynamics study of water nanodroplets under the influence of an externally applied electric field. Our simulations cover a wide range of droplet sizes and electric field strengths, which allows for a thorough exploration of the structural and energetic behavior of nanodroplets in the presence of an external electric field. Our analysis reveals the molecular-level mechanism behind the shape extension of a nanodroplet from a spheroid to a highly prolate ellipsoid as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…For example, investigations into the shape and behaviour of water droplets in strong EFs have grown due to their relevance to a variety of applications including electrospinning and inkjet printing. 89,105 All-atom classical MD simulations have proven useful in studying the structural and energetic behaviour of water nanodroplets under the influence of an externally applied static EFs. 105 The study identified the molecular mechanism responsible for shape extension of a nanodroplet from a spheroid to a highly prolate ellipsoid when exposed to 0.9 V nm −1 EF (see Fig.…”
Section: Recent Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, investigations into the shape and behaviour of water droplets in strong EFs have grown due to their relevance to a variety of applications including electrospinning and inkjet printing. 89,105 All-atom classical MD simulations have proven useful in studying the structural and energetic behaviour of water nanodroplets under the influence of an externally applied static EFs. 105 The study identified the molecular mechanism responsible for shape extension of a nanodroplet from a spheroid to a highly prolate ellipsoid when exposed to 0.9 V nm −1 EF (see Fig.…”
Section: Recent Case Studiesmentioning
confidence: 99%
“…89,105 All-atom classical MD simulations have proven useful in studying the structural and energetic behaviour of water nanodroplets under the influence of an externally applied static EFs. 105 The study identified the molecular mechanism responsible for shape extension of a nanodroplet from a spheroid to a highly prolate ellipsoid when exposed to 0.9 V nm −1 EF (see Fig. 2) to be due to the propensity of the water dipoles to align with the electric field while simultaneously restructuring to minimize the dipole–dipole interaction energy.…”
Section: Recent Case Studiesmentioning
confidence: 99%
“…According to the research on electrowetting under a square-pulsed electric field, the droplets can bounce more effectively under AC electric field by adjusting the voltage pulse width. , However, it has been reported that the lift-off mechanism of macrodroplets under a perpendicular electric field is the charge accumulation in the droplet and decrease in contact angle. ,, That is not suitable for nanodroplets because the electric double layer can hardly form at the nanoscale . Besides, the polarization of water molecules under the electric field contributes to the severe deformation of nanodroplets . Due to the polarized water molecules in the droplet being directionally arranged, the dipole moment has a tendency to deflect along the direction of the electric field .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the polarization of water molecules under the electric field contributes to the severe deformation of nanodroplets . Due to the polarized water molecules in the droplet being directionally arranged, the dipole moment has a tendency to deflect along the direction of the electric field . As the intensity of the electric field increases, the polarization of water droplets is enhanced, resulting in three kinds deformation of droplets, namely, spheroid, ellipsoid, and column.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The electric field can change the directional polarization of interfacial molecules, and affect the formation of hydrogen bonds. In addition to the electric field intensity, the solubility of ions in the droplets, [27][28][29] the field direction, [30][31][32][33] the material properties of the solid surfaces [34][35][36][37][38][39] and thermal fluctuations [40,41] also affect the state of droplets. The nanodroplets in confined spaces exhibit more complicated evolution dynamics.…”
Section: Introductionmentioning
confidence: 99%